2022
DOI: 10.1016/j.seppur.2021.120246
|View full text |Cite
|
Sign up to set email alerts
|

Redox-active metal-organic frameworks for the removal of contaminants of emerging concern

Abstract: The pollution due to the presence of contaminants of emerging concern (CECs) is a major cause for concern because of the serious threat it supposes to human health and ecosystem functions. Many efforts have been geared toward their removal to guarantee safer freshwater.Metal-organic frameworks (MOFs) are crystalline hybrid materials with high surface area and flexible rational design, which allows the incorporation of different active sites into a particular framework, thereby emerging as a potentially excelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 196 publications
0
8
0
Order By: Relevance
“…Fenton and Fenton-like reaction using nanomaterials advanced catalytic oxidation of organic pollutants for degradation and water treatment [10,15]. These reactions are called advanced oxidation processes (AOPs) [16]. The reaction generates highly oxygen reactive species (ROS) or hydroxyl radicals ( • OH) via the reaction between a catalyst and H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Fenton and Fenton-like reaction using nanomaterials advanced catalytic oxidation of organic pollutants for degradation and water treatment [10,15]. These reactions are called advanced oxidation processes (AOPs) [16]. The reaction generates highly oxygen reactive species (ROS) or hydroxyl radicals ( • OH) via the reaction between a catalyst and H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Recently, iron-containing MOFs (Fe-MOFs) have been widely used for the photocatalytic activation of PMS/PDS due to their diverse structures, good stability, and low cost. 11,12 Zhang et al reported a photocatalytic system with MIL-88A(Fe) as a photocatalyst for the degradation of tetracycline hydrochloride. 13 The photogenerated electrons (e À ) could be captured by PDS to generate SO 4 À radicals, which improved the degradation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide has been exploited as a semiconductor for water photocatalytic applications due to its abundance, inexpensiveness, low toxicity, and bandgap energy of approximately 3.2 eV, which allows photo-excitation with radiation up to 387 nm [ 13 ]. However, great efforts have been paid to overcome the main limitations of titanium dioxide as a semiconductor, i.e., limited absorption of the solar spectrum in the visible region and the high recombination rate of the photo-generated electron–hole pair [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metal–Organic Frameworks (MOFs) are porous structures built by metal oxo clusters or secondary building units (SBU) and organic linkers acting as a bridge between the SBU. As a result, a highly porous structure with active redox behavior is produced, which can be used as a potential photocatalyst for water purification [ 13 , 17 ]. MOFs display the advantage of an easy design of certain properties such as the size of the porous cages by selecting appropriate organic ligands, or the tuning of the photocatalytic response by the functionalization of the ligand with certain organic groups.…”
Section: Introductionmentioning
confidence: 99%